Analisa Pengaruh Size Perusahaan, Capital Adequacy Ratio (CAR), Non Perfoming Financing (NPF), Return On Asset (ROA), Financing Deposit Ratio (FDR) Terhadap Pengungkapan Corporate Social Responsibility (CSR) Bank Umum Syariah di Indonesia Periode 2012-201 - Ade Sofyan Mulazid (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
Abstract This study aimed to analyze the influence SizePerusahaan, Capital Adequacy Ratio (CAR), non performing Financing (NPF), Return on Assets (ROA), Financing to Deposit Ratio (FDR) on the disclosure of Corporate Social Responsibility (CSR) Islamic Banks in Indonesia period 2012- 2015. Corporate Social Responsibility (CSR) is a form of the company in its operations by focusing on economy, society and environment. The sample in this study amounted to 11 public Islamic Bank in this Indonesia.Penelitian panel regression analysis method. The model chosen in this study is the fixed effect model (fixed effect). Based on the analysis that has been done in getting results simultaneously all the independent variables are the size of the Bank, Capital Adequacy Ratio (CAR), non performing Financing (NPF), Return on Assets (ROA), Financing to Deposit Ratio (FDR) which affect the disclosure of CSR. However, the size of the company and Financing to Deposit Ratio (FDR) affect the Bank's CSR disclosure. Capital adequacy ratio (CAR), Non Performing Financing (NPF), return on assets (ROA) has no effect on the disclosure of CSR. Keyword: Corporate Social Responsibility (CSR), Size, Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Assets (ROA), Financing to Deposite Ratio (FDR).